A review of design methodologies for manufacturing systems - Alves, Anabela Carvalho (2009)
This paper presents a review of design methodologies for manufacturing systems, with focus on Product Oriented Manufacturing Systems (POMS). POMS organization is discussed and compared against function oriented manufacturing. The methodologies for manufacturing systems design are described and grouped in three classes: generic, specific and product oriented focused. Several methodologies in the first class are referred. They tend to be suitable for whatever kind of product that is necessary to develop or design, including manufacturing systems. Usually, they arrive to a general, conceptual first approximation manufacturing system solution, which need refinement. Manufacturing systems specific methodologies are more objective being able to offer a clearer picture of the manufacturing system ultimate solution. A number of them are reviewed. The product focused class of the manufacturing systems design methodologies is divided in two groups: methodologies for designing new manufacturing systems, referred as construction methodologies, and methodologies for reengineering or reconfiguring existing ones. A few methodologies are referred and a methodology referred as the GCD methodology is explained in more detail due to its particular focus on POMS design. Through it a better understanding is given of the POMS design needs. The GCD methodology is also put in perspective in relation to other reviewed methodologies.